Deep Breathing Exercise with and without Sustained Maximum Inspiration on Vital Signs in Chronic Obstructive Pulmonary Disease - Suci Amanati (Jurnal Respirologi Indonesia, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is characterized by airflow obstruction that impairs oxygenation and alters vital signs. Pulmonary rehabilitation commonly includes Deep Breathing Exercise (DBE), while Sustained Maximum Inspiration (SMI) may further enhance lung expansion and oxygen diffusion. This study aimed to compare the effects of DBE alone and DBE combined with SMI on vital signs in patients with COPD. Methods: A quasi-experimental study was conducted over four weeks at the Community of Pulmonary Health Care, Semarang, involving 22 eligible COPD patients. Participants were divided into two groups: DBE only (n = 11) and DBE with SMI (n = 11). Both groups performed daily breathing exercises for 10 minutes. Vital signs measured before and after the intervention included blood pressure, heart rate, respiratory rate, and oxygen saturation. Data were analyzed using paired and independent t-tests with a significance level of p < 0.05. Results: The DBE group experienced nonsignificant reductions in blood pressure and respiratory rate, along with a slight, nonsignificant decrease in oxygen saturation. The DBE with SMI group showed reductions in blood pressure and respiratory rate and a significant improvement in oxygen saturation. Between-group comparisons revealed no significant differences in blood pressure, heart rate, or respiratory rate, but oxygen saturation was significantly higher in the DBE with SMI group. Conclusion: Both DBE and DBE combined with SMI positively influence vital signs in COPD patients. However, incorporating SMI into DBE provides additional benefits, particularly in improving oxygen saturation.